Development of Road Networks to Support the Development of the Government Center in the Capital City of Nusantara (IKN) - Saleh, Arbillah; Djakfar, Ludfi; Wicaksono, Ahcmad (Rekayasa Sipil, 2025)
The Indonesian government has designated the relocation of the capital city to East Kalimantan through Law No. 3 of 2022. Developing the Central Government Core Area (KIPP) within the new capital city of Nusantara (IKN) in East Kalimantan presents significant challenges and opportunities in transportation planning. This study evaluates the performance of existing and proposed road networks using integrated macro- and micro-simulation tools: CUBE Voyager and PTV VISSIM. CUBE Voyager is used for trip generation, distribution, and highway assignment, while PTV VISSIM simulates intersection performance based on detailed geometry and traffic behavior. Results indicate that without the development, key national roads such as Soekarno–Hatta will experience overcapacity by 2035, with a volume-to-capacity ratio (VCR) exceeding 1. However, traffic performance improves significantly by adding toll roads and new internal road networks. Notably, 71.7% of vehicles on the Sp. ITCI–Sp. The Riko segment is projected to shift to the toll road. Internally, KIPP's one-way road system maintains Level of Service (LOS) A through 2035, while intersections generally operate at LOS B, with one key intersection at LOS C. The findings emphasize the importance of integrated planning between land use and transportation, highlighting the role of multimodal networks and optimized traffic management strategies in supporting the future capital’s mobility and resilience. This study recommends sustainable road network development to ensure transportation efficiency in the new capital city area.